The analysis of modus operandi and the attempt to determine the perpetrator’s motives based on the case study of the unexplained crime with the codename ‘Partner’ - Berdzik, Tomasz (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The article is an attempt to interpret the information collected on the basis of the contents of scientific materials in confrontation with widely available press reports and media files regarding the largest unexplained series of murders in the history of Polish forensic science, which for the sake of the investigation are the case messages authorized by the authorities working on the case being a fraction of the material collected since the start of the investigation, but sufficient to satisfy the right to public information, as well as social curiosity. Based on the above documentation, some questions have been posed that get answers because of an incomplete outline of the perpetrators and especially individuals who handle not fluent in fields of study such as criminology, forensics, forensic medicine and criminal psychology. Some changes that take place because of the passage of time and new threads around the investigation have been discussed.